2004
DOI: 10.1002/elps.200305746
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the cis‐trans isomerization barrier of enalaprilat by dynamic capillary electrophoresis and computer simulation

Abstract: Dynamic capillary electrophoresis (DCE) and computer simulation of the elution profiles with the stochastic model has been applied to determine the isomerization barriers of the angiotensin converting enzyme inhibitor enalaprilat. The separation of the rotational cis-trans isomeric drug has been performed in an aqueous 20 mM borate buffer at pH 9.3. Interconversion profiles featuring plateau formation and peak broadening were observed. To evaluate the rate constants k(cis-->trans) and k(trans-->cis) of the cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Therefore, it is statistically not very probable to find compounds that, being different, can have exactly the same molecular mass and electrophoretic mobility (not even positional isomers, as repeatedly demonstrated in the CE literature, see e.g. [33]). Finally, in regard to our comment that future simulations on the steady-state distribution of CAs should include mixtures of good and poor CAs, it has been pointed out that this has been already done [34].…”
Section: Note Addedmentioning
confidence: 87%
“…Therefore, it is statistically not very probable to find compounds that, being different, can have exactly the same molecular mass and electrophoretic mobility (not even positional isomers, as repeatedly demonstrated in the CE literature, see e.g. [33]). Finally, in regard to our comment that future simulations on the steady-state distribution of CAs should include mixtures of good and poor CAs, it has been pointed out that this has been already done [34].…”
Section: Note Addedmentioning
confidence: 87%
“…As the cis-trans interconversion occurs within the time scale of partitioning, a plateau formation between the two separated peaks of the isomers can be observed [95]. The first kinetic investigation was done by Trapp et al [96]. It was found that in the investigated temperature range the peak ratio of the isomers is temperature dependent and the peak area of the first eluted isomer decreases with increasing temperature (cf.…”
Section: Drugsmentioning
confidence: 97%
“…Therefore, the elution order of the isomers should be trans before cis according to IUPAC rules [98]. The kinetic parameters were obtained by computer simulation of the experimental electropherograms and are summarized in Table 4 [96].…”
Section: Drugsmentioning
confidence: 99%
“…4. With this approach, Schurig and coworkers [23,24] were able to estimate the rate constants for isomerization of AlaPro, Leu-Pro, and Phe-Pro between 0 and 207C as well as for the isomerization of the enzyme inhibitor enalaprit between 0 and 157C. The reported values of k f (cis ?…”
Section: Chromwinmentioning
confidence: 96%